Assessment of Essential Oils Against Bacterial Leaf Blight of Rice (Journal of Plant Disease Sciences, 2023)
The experiment was designed in a randomized block design with ten treatments replicated three times, and all packages of practices were followed while carrying out the experiment. Ten treatments, namely, T1: Citronella oil (2 ml/l), T2: Eucalyptus oil (2 ml/l), T3: Cedar wood oil (2 ml/l), T4: Nirgundi oil (2 ml/l), T5: Lemon grass oil (2 ml/l), T6: Clove oil (2 ml/l). T7- Neem oil at 2 ml/l, T8- Emulsifier at 2 ml/l, T9- Carbendazim at 1 g/l, and T10- untreated control were tested against bacterial leaf blight of rice on the most widely grown variety TN-1. Among the various essential oils tested to control bacterial leaf blight studies revealed that treatment T2 (Eucalyptus oil @2 ml/l) had the lowest incidence of bacterial leaf blight of rice with 38.89% disease incidence as compared to control (58.52%) with the highest disease reduction over control to the tune of 33.54% and was statistically significant over the othertreatments.
Keywords: Rice; Bacterial leaf blight; Essential oil; Efficacy